2009
DOI: 10.1103/physrevb.79.125406
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent elasticity of nanocrystalline titania

Abstract: Synchrotron-based high-pressure x-ray diffraction measurements indicate that compressibility, a fundamental materials property, can have a size-specific minimum value. The bulk modulus of nanocrystalline titania has a maximum at particle size of 15 nm. This can be explained by dislocation behavior because very high dislocation contents can be achieved when shear stress induced within nanoparticles counters the repulsion between dislocations. As particle size decreases, compression increasingly generates disloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
79
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 51 publications
9
79
3
Order By: Relevance
“…This suggests that the proposed scaling of properties might be applicable to a wide range of nanocrystalline solids. Experiments have already measured grain-size dependent elastic moduli [20,21]. We hope that theory and simulations of the kind we present here will assist experimentalists in synthesising new nanomaterials with better properties.…”
Section: /3mentioning
confidence: 91%
“…This suggests that the proposed scaling of properties might be applicable to a wide range of nanocrystalline solids. Experiments have already measured grain-size dependent elastic moduli [20,21]. We hope that theory and simulations of the kind we present here will assist experimentalists in synthesising new nanomaterials with better properties.…”
Section: /3mentioning
confidence: 91%
“…Chen et al [52] recently showed that the bulk modulus (B = 1 K T ) of anatase nanoparticles has a distinct size dependence. It was found that the B increases as the particle diameter L decreases down to 15 nm where it attains a maximum, and then sharply decreases at smaller L. The decreased compressibility K T down to L = 15 nm was explained as due to an increasing amount of strained regions in the nanoparticles such as dislocations which can resist compression since these atoms are already displaced from their neutral positions.…”
Section: Surface-stress-modified Phonon Confinement Model (Ss-pcm)mentioning
confidence: 99%
“…[53] A positive f indicates that the surface is under tension, which implies lattice contraction. [49] The bulk modulus is reported to be B ≈ 240 GPa, [52] and the mode Grüneisen parameter has previously been reported to be γ i = 4.23. [40] Considering that f × K T = f × 1/B ≈ constant (see discussion in the Models section), i.e.…”
Section: Comparisons Of the Pcm And Ss-pcmmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of reduced properties, this is due to the inverse Hall-Petch effect [52][53][54] where, yield strength and hardness below a critical grain size decreases with grain size. This occurs as the grain is too small to support the pile up of dislocations at grain boundaries and a high enough density of dislocations to resist deformation.…”
Section: Mechanical Behavior Studies Of Nano-objects and Thin Filmsmentioning
confidence: 96%